Alexander Polyhistor and Glaucus of Rhegium as Sources of Pseudo-Plutarch’s Treatise De musica. III–IV - Almazova, Nina (Hyperboreus, 2022)
Further arguments are adduced in support of the thesis (see Hyperboreus 27: 2 [2021] 266–290) that Ps.-Plutarch extensively used the “Collection of Information about Phrygia” by Alexander Polyhistor for his history of music in De mus. ch. 3–10, and it is in Polyhistor’s work that he found all the quotations from Glaucus of Rhegium concerning the impact of Olympus. The acquaintance of Ps.-Plutarch with the work of Glaucus at first hand is dismissed on the following grounds: (a) the way of introducing his quotations such as using the indefinite pronoun τινι (p. 4, 27 Ziegler 1959) and making Glaucus’ statement governed by Ἀλέξανδρος … ἔφη (p. 5, 3–4), and (b) Ps.-Plutarch’s total inability to insert extant data logically into the argument (as seen throughout the first section of his treatise), whereas some references to Glaucus do form an organic part of the discussion. Glaucus’ statement of Olympus’ influence on Thaletas in ch. 10 is so similar to that of his influence on Stesichorus in ch. 7 that they must have belonged together in the original work and were probably adduced together in Ps.-Plutarch’s source. Although on the whole the matters discussed in ch. 9–10 are unlikely to have been taken from a treatise about Phrygia, Glaucus’ quotations concerning Thaletas and Xenocritus seem to make no contribution to the current discussion on genres. Thus, the compiler might simply have been inspired by coming across the same names, leading him to insert the information from Alexander’s work mechanically (the same was the case with the reference to Terpander that prompted a rather irrelevant insertion of Polyhistor’s data in ch. 5).